Oral History of Pak Rashid: A Valuable Historical Documentation Process of Cikgu Rashid - Universiti Putra Malaysia, Pejabat Strategi Korporat dan Komunikasi (Pusat Strategi Dan Perhubungan Korporat, Universiti Putra Malaysia, 2025)
SHAH ALAM - The Alumni Relations Centre (ARCUPM) in collaboration with the Sultan Abdul Samad Library, University Putra Malaysia (UPM), conducted an oral history interview session with Tuan Haji Mohamed Ismail, an alumnus of UPM, Class of 1967.